Influence of remote earth and impulse polarity on earthing systems by field measurement - Abdullah S.; Nor N.M.; Agbor N.; Reffin M.; Marinah Othman (Institution of Engineering and Technology, 2024)
There has been a vast vacuum in the literature on the importance of the location of remote earth carried out during impulse test on grounding systems using field measurements. Some published work show that the remote earth is installed surrounding the electrode under tests, whilst some have used separate remote earth, away from it. This work studies the impact of return electrode location on transient behaviour of the earthing electrode. The electrode under test is a single rod. Two types of remote earth configurations are used, a circular electrode with multiple rods surrounding the single rod, and one that is 80 m away from it. Impulse tests are conducted under both impulse polarities. Voltage and current traces are captured for a single rod, using two different types of remote earth configurations, with the impulse resistance measured as well. It has been established that the arrangement of the remote earth poses no influence on the test results. That said, higher oscillations of current traces and higher resistance values have been observed in negative impulse in comparison with positive impulse polarities. The Institution of Engineering and Technology 2018.